Global trends and hotspots of phage therapy for bacterial infection: A bibliometric visualized analysis from 2001 to 2021 - Maimaiti, Zulipikaer; Li, Zhuo; Xu, Chi; Chen, Jiying; Chai, Wei (Frontiers in Microbiology, 2023)
ABSTRACT Background: Antibiotic resistance is one of the main global threats to human health, and just the development of new antimicrobial medications is not enough to solve the crisis. Phage therapy (PT), a safe and effective treatment method, has reignited the interest of researchers due to its efficacy in the clinical treatment of drug-resistant bacterial infections. There is, however, no bibliometric analysis of the overall trends on this topic. Therefore, this study aims to provide an overview of the current state of development and research in this area. Methods: We extracted all relevant publications from the Web of Science Core Collection (WoSCC) database between 2001 and 2021. We performed bibliometric analysis and visualization using Cite Space, VOS viewer, and R software. Annual trends of publications, countries/regions distributions, institutions, funding agencies, co-cited journals, author contributions, core journals, references, and keywords were analyzed. Results: A total of 6538 papers were enrolled in this study, including 5364 articles and 1174 reviews. Publications have increased drastically from 61 in 2001 to 937 in 2021, with 3659 articles published in the last five years. North America, Western Europe, and East Asia were significant contributor regions. The USA, China, and the UK were the most productive countries. The Polish Academy of Sciences was the most contributive institution. Frontiers in Microbiology and Applied and Environmental Microbiology were the most productive and co-cited journals. Gorski A and Lavigne R published most articles in this field, while Fischetti VA was the author with the most cited. Regarding keywords, research focuses include phage biology, phage against clinically important pathogens, phage lysis proteins, phage therapy, biofilm-related research, and recent clinical applications. Conclusion: PT is a potential strategy for combating antibiotic resistance, and it will provide us with an alternative therapeutic option for bacterial infection. According to global trends, the scientific output of PT in bacterial infections is increasing, with developed countries such as the USA leading the way in this area. Although the safety and efficacy of PT have been proven, more clinical trials on the phages against infectious diseases caused by various pathogens are still needed.